2002
DOI: 10.1902/jop.2002.73.5.551
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarker Evidence of Oxidative DNA Damage in Whole Saliva From Clinically Healthy and Periodontally Diseased Individuals

Abstract: In the present study, we evaluated for the first time 8-OHdG levels in whole saliva of patients with periodontitis and assessed changes after initial periodontal treatment. Our study indicated that 8-OHdG levels in saliva appear to reflect the status of periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
141
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 21 publications
19
141
5
1
Order By: Relevance
“…Our study showed that the salivary 8-OHdG levels were significantly higher in the periodontitis patients than in the healthy controls. This result confirms findings of limited previous studies (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Also, we detected the 5-kbp mtDNA deletion in the gingival tissues of 20 of the 32 periodontitis patients and did not detect the 7-kbp mtDNA deletion in the periodontitis patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study showed that the salivary 8-OHdG levels were significantly higher in the periodontitis patients than in the healthy controls. This result confirms findings of limited previous studies (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Also, we detected the 5-kbp mtDNA deletion in the gingival tissues of 20 of the 32 periodontitis patients and did not detect the 7-kbp mtDNA deletion in the periodontitis patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, information on markers of ROS reactions with DNA in periodontitis is limited. The majority of published data on oxidative damage to DNA has been reported by a Japanese group who investigated 8-OHdG levels in the saliva of periodontitis patients (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Their studies demonstrated that salivary levels of 8-OHdG in samples from subjects with CP were significantly higher than those from periodontally healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In association with oral and dental diseases (especially periodontitis), changed oxidative stress markers in saliva were reported [2,46,51]. Being a noninvasive biofluid, saliva allows easy, noninvasive and safe sam-ple collection.…”
Section: Introductionmentioning
confidence: 99%
“…periodontitis) and systemic (e.g. diabetes, inflammatory bowel disease) conditions (Arana et al 2006;Bahar et al 2007;Celec et al 2005;Gorelik et al 2007;Jahanshahi et al 2004;Kolarzyk et al 2006;Mashayekhi et al 2005;Nagler et al 2000;Reznick et al 2006;Ryo et al 2006;Sawamoto et al 2005;Sculley and Langley-Evans 2003;Sugano et al 2003;Takane et al 2002;Tsai et al 2005). Changes in salivary cortisol secretion patterns (Fiocco et al 2006;Giubilei et al 2001;Hatfield et al 2004;Porter et al 2002;Scherder et al 2006;Wolf et al 2002;Woods and Dimond 2002), amylase activity (Sramek et al 1995), and acetylcholinesterase activity (Sayer et al 2004) have been documented in persons with AD or MCI, attesting to the plausibility of exploiting saliva for neurodegenerative disease biomarker discovery.…”
Section: Introductionmentioning
confidence: 99%